EVALUATION OF ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF PARIS POLYPHYLLA SM. - MAYIRNAO, HOM-SINGLI; BHAT, ARBEEN AHMAD (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Paris polyphylla Sm. is a very important anti-cancerous plant species found in the Himalayan region of India. The present study was carried out to determine the phenolic and flavonoid content, antioxidant and antimicrobial activity of its rhizome. Methods: Antioxidant activity of rhizome extract was evaluated through 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. Antimicrobial activity was evaluated through disc diffusion assay against two bacterial and two fungal strains. The bacterial species used in the present study were Escherichia coli and Staphylococcus aureus and the fungal strains used were Aspergillus niger and Trichoderma reesei. Results: The standard curve of Gallic acid revealed that the phenolic content of our sample is 43.01±0.17 mg Gallic acid equivalents (GAE)/g dry weight (DW). Similarly, flavonoids were obtained as 28±0.12 mg quercetin equivalent/g DW of the sample. It was observed that the methanolic rhizome extract showed higher antioxidant potential than water extract with the IC50 value of 1.09 mg/ml. Further, the rhizome extract of P. polyphylla species exhibited significant antimicrobial activity and it was observed that at concentration of 5 mg/ml of the sample, the percentage inhibition was 95-97% in E. coli, S. aureus and A. niger whereas in case of T. reesei it was 74%. Conclusion: This study is first of its kind in the Indian subcontinent on this plant species and these findings indicate the tremendous and promising potential of this wonder herb. A lot of work has already been done in China on this species, therefore, further studies are required for the conservation and sustainable use in Indian subcontinent before this species is thrown into extinction as it has already been declared vulnerable.